2018
DOI: 10.1371/journal.pone.0206807
|View full text |Cite
|
Sign up to set email alerts
|

Changes in brain white matter structure are associated with urine proteins in urologic chronic pelvic pain syndrome (UCPPS): A MAPP Network study

Abstract: The Multidisciplinary Approach to the Study of Chronic Pelvic Pain (MAPP) Research Network has yielded neuroimaging and urinary biomarker findings that highlight unique alterations in brain structure and in urinary proteins related to tissue remodeling and vascular structure in patients with Urological Chronic Pelvic Pain Syndrome (UCPPS). We hypothesized that localized changes in diffusion tensor imaging (DTI) measurements might be associated with corresponding changes in urinary protein levels in UCPPS. To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…The resulting SPMs were thresholded at a level of significance p <0.05 for each contrast of interest, and a cluster size threshold greater than 250 μL. This minimum cluster size is similar to previous studies using cluster-based permutation correction [ 21 23 ], while also trying to maximize the sensitivity to DTI changes.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting SPMs were thresholded at a level of significance p <0.05 for each contrast of interest, and a cluster size threshold greater than 250 μL. This minimum cluster size is similar to previous studies using cluster-based permutation correction [ 21 23 ], while also trying to maximize the sensitivity to DTI changes.…”
Section: Methodsmentioning
confidence: 99%
“…The inherently unnatural setting of lying supine for fMRI and UDS is a confounding factor that may make it difficult to void for both healthy individuals and especially MS patients who already difficulties voiding. Supine positioning, UDS catheters, and supraphysiologic bladder filling might affect the activation map of different brain regions and subsequently the FC analysis, even though DTI signals in white matter in similar studies have not been found to be altered by these quick dynamic variations [ 33 , 34 ]. Additionally, DTI captures anatomical parameters of the brain, which are not thought to vary as much as FC does [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supine positioning, UDS catheters, and supraphysiologic bladder filling might affect the activation map of different brain regions and subsequently the FC analysis, even though DTI signals in white matter in similar studies have not been found to be altered by these quick dynamic variations. [32,33] Additionally, DTI captures anatomical parameters of the brain, which are not thought to vary as much as functional connectivity does. [34] As previously mentioned, our study does not address spinal lesions and the major effects they may have on sensory and motor function.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Inclusion criteria: (a) IS symptoms occur for the rst time, such as limb weakness or numbness, facial numbness or angle of mouth, slurred speech or di culty in understanding language, eyes staring to one side, loss or blurred vision in one or both eyes, dizziness and vomiting, severe headaches that are rare in the past, vomiting, disturbance of consciousness or convulsions. (b) The diagnosis complied with the AHA/ASA "2019 Update to the 2018 Guidelines for the Early Management of Acute Ischemic Stroke" [19]. The cranial computed tomography examination on admission ruled out the cerebral hemorrhage, but found low-density cortical infarcts or wedge-shaped lacuna edges , band-shaped low-density infarcts, unclear boundary between the basal cortex and surrounding white matter, or the boundary of the lenticular nucleus or even the entire insular lobe structure, without intracranial space-occupying lesions; or the cortex layered punctate or aky high signal (fresh lesions) was found by diffusion-weighted magnetic resonance imaging (DWMRI).…”
Section: Methodsmentioning
confidence: 99%